From Rapid to Delayed and Remote Postconditioning: The Evolving Concept of Ischemic Postconditioning in Brain Ischemia - Zhao, Heng; Ren, Chuancheng; Chen, Xingmiao; Shen, Jiangang (Current Drug Targets, 2012)
Ischemic postconditioning is a concept originally defined to contrast with that of ischemic preconditioning. While both preconditioning and postconditioning confer a neuroprotective effect on brain ischemia, preconditioning is a sublethal insult performed in advance of brain ischemia, and postconditioning, which conventionally refers to a series of brief occlusions and reperfusions of the blood vessels, is conducted after ischemia/reperfusion. In this article, we first briefly review the history of preconditioning, including the experimentation that initially uncovered its neuroprotective effects and later revealed its underlying mechanisms-of-action. We then discuss how preconditioning research evolved into that of postconditioning - a concept that now represents a broad range of stimuli or triggers, including delayed postconditioning, pharmacological postconditioning, remote postconditioning - and its underlying protective mechanisms involving the Akt, MAPK, PKC and KATP channel cell-signaling pathways. Because the concept of postconditioning is so closely associated with that of preconditioning, and both share some common protective mechanisms, we also discuss whether a combination of preconditioning and postconditioning offers greater protection than preconditioning or postconditioning alone.
Keywords: heart